Women in Serbia: In the gap between patriarchal and new roles - Torlak, Nada (Napredak, 2020)
Although we have entered the third millennium long ago, women in Serbia are still in an imbalance between old, traditional roles and new values. Instead of being relieved in the 21st century, it seems like it has never been harder for a woman. Lost between old patriarchal relations and obligations, she also got some new ones. In addition to the traditional (implicit) roles of wife, mother and housewife, now the already common (covered in the movie) question arises: what do women want? To be family, career, and leadership position pillars or all of that combined. However, this question is not only addressed to them, but to the wider social community, or the entire country. Why? Because the old roles have remained, and the new, professional ones mean an equal race with men, with an exception of earnings and few other things. In this paper, we will try to answer these questions or at least point out the existing problems, including already mentioned gap and different challenges a modern woman in Serbia is facing.